Individualized and inverse optimized needle configuration for combined intracavitary-interstitial brachytherapy in locally advanced cervical cancer. - Zhang, Daguang; Yang, Zhiyong; Jiang, Shan; Zhou, Lin; Zhou, Zeyang; Wang, Wei (Journal of Cancer Research & Therapeutics, 2019)
Objectives: The aim of this study is to address the limitation of combined intracavitary-interstitial (IC/IS) brachytherapy (BT) in locally advanced cervical cancer using standardized applicators and to determine the optimal dose distribution in patients with challenging tumors, innovative methods of customizing and optimizing the IS needle configuration for combined IC/IS BT are proposed and investigated.Materials and Methods: A software module that could customize the IS needle configuration and subsequently generate the digital model of guiding template for three-dimensional printing was developed and integrated into our in-house treatment planning system for BT. The inverse optimization method based on the technique of mixed-integer linear programming was introduced to determine the needle tracks out of a candidate pool and dwell times at corresponding locations to best meet dose objectives. A treatment planning study was conducted to evaluate the feasibility and performance of the proposed methods.Results: The workflow for combined IC/IS BT with customized and inverse optimized IS needle configuration was presented. Dosimetric results of the treatment planning study showed that sufficient target coverage could be obtained with the customized IS needle configuration for challenging cases. The proposed dose-based optimization method for IS needle configuration was feasible and effective. Improved target coverage and organ-at-risk sparing were achieved using the inverse planning method.Conclusions: Using the proposed methods of customizing and optimizing the IS needle configuration, the limitation in the standardized design of combined IC/IS applicators can be addressed, and sufficient target coverage is obtained in cervical cancer patients with unfavorable tumor topography and/or extra lateral expansion.